Réponses

  • Utilisateur Brainly
2014-09-09T06:48:30+02:00
A= - 3 - 8
A= - 11

B= - 3 + 8
B= 5

C= 3 - 8
C= - 5

H= (- 3) + (- 8) - (- 12) + (- 4) - (+ 27)
H= 3 - 8 + 12 - 4 - 27
H= - 24

G= (+ 45) - (- 69) + (- 27) + (- 1,5) - (- 456)
G= 45 + 69 - 27 - 1,5 + 456
G= 541,5
Dans H c'est -3, tu l'as oublié dans la deuxième expression
Meilleure réponse !
2014-09-09T08:28:56+02:00
A = -3 - 8 
A = - 11

B = - 3 + 8 
B = 5

C = 3 - 8 
C = - 5

H = (- 3) + (+ 8) - (- 12) + (- 4) - (+ 27)
H = - 3 + 8 + 12 - 4 - 27
H = - 3 - 27 - 4 + 8 + 12
H = - 34 + 20
H = - 14

G = (+ 45) - (- 69) + (- 27) + (- 1,5) - (- 456)
G = 45 + 69 - 27 - 1,5 + 456
G = 45 + 456 + 69 - 27 - 1,5
G = 570 - 28,5
G = 541,5